PENGARUH KEPADATAN SEBAR BENIH, KOMPOSISI, DAN KETEBALAN MEDIA SEMAI PADA SISTEM DAPOG, PENANAMAN DENGAN TRANSPLANTER INDOJARWO TERHADAP HASIL TANAM JAJAR LEGOWO 2:1 - Suharno, Suharno; Hidayat, Rohmat; Nasution, Hinandang (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2017)
The research aims to know treatment combination influence of media composition, media thickness, and paddy seeds density on the result of planting seen from the seed amount per hole, plant depth and level of clumsiness with indojarwo trans planter 2: 1. This research was conducted in Celeban, Agricultural Extension College, Yogyakarta. This research was performed from October 30, 2016 to November 17, 2016. The research method arranged in base pattern Randomized Complete Block Design, consisting 3 factors. The first factor is the composition on media (P), consists of 3 level types, soil 1,5: compost 0,5 (P1), soil 1: compost 1 (P2), soil 0,5: compost 1,5 (P3). The second factor is the thickness of media (M), consists of 3 types, media 1 cm and cover 0,5 cm (MI), media 1,5 cm and cover 0,5 cm (M2), media 2cm and cover 0,5cm (M3). The third factor is the density of paddy seeds (K) consists of 3 types, 60 g/ dapog (KI), 70 g/ dapog (K2) and 80 g/dapog (K3). Each combination receives 2 times treatment, total 54 units of treatment. Statistical analysis was conducted to determine the influence difference between treatment with diverse examination 5% and 1 % and to know the real difference between treatments with 5 % DMR test. The result of the research combination treatment of comparison/ composition seedlings media (P), media seedlings thickness (M), and seed density (K) had no significant effect on the average number of seeds per hole, the average plant dept, and average of seed stands on rice plant. The combination of the treatment of comparison/ composition seedlings (P), the thickness of seedlings (M), and seed density (K) that showed the best result of planting with trans planter parameter number seed/ hole that is combination of P1M2K2, plant dept parameter that is combination P3M2K3, and seed stands parameter on rice plant combination is P3M2K3. Number of seed/holes, depth of planting, and the seed stand of rice plant with trans planter planting, influenced by other factors, its land preparation factor.